1976
DOI: 10.1161/01.cir.53.3.483
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial lesions of progressive systemic sclerosis. A cause of cardiac dysfunction.

Abstract: The nature, prevalence, functional significance, and indeed existence of myocardial disease in progressive systemic sclerosis (PSS) has been debated. In this study the clinical and pathological features of 52 autopsied patients were analyzed in an attempt to resolve these questions. A distinctive focal myocardial lesion ranging from contraction band necrosis to replacement fibrosis throughout both ventricular walls was present in 23 patients who had widely patent extramural coronary arteries. There were no mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
155
0
4

Year Published

1978
1978
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 392 publications
(163 citation statements)
references
References 22 publications
4
155
0
4
Order By: Relevance
“…Active inflammation, however, is rarely if ever observed in autopsy studies of myocardial lesions in patients with scleroderma (1,2,4). This may be explained by the relative rarity of inflammatory myositis in scleroderma, as well as by the fact that we could find no autopsy report in which the heart was examined during active myositis.…”
Section: Discussionmentioning
confidence: 90%
“…Active inflammation, however, is rarely if ever observed in autopsy studies of myocardial lesions in patients with scleroderma (1,2,4). This may be explained by the relative rarity of inflammatory myositis in scleroderma, as well as by the fact that we could find no autopsy report in which the heart was examined during active myositis.…”
Section: Discussionmentioning
confidence: 90%
“…Although other possible explanations for perfusion defects would theoretically include intimal prolifera-ANVARI ET AL tion or disseminated intravascular coagulation of the small coronary arteries as described in the literature (16), one cannot rule out the possibility that there may have been epicardial coronary disease. Furthermore, intermittent ischemia due to coronary artery spasm is known to occur in anatomically normal coronary arteries (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Impaired coronary artery reserve has previously been demonstrated in SSc patients by noninvasive imaging techniques (5)(6)(7). Studies published a few decades ago suggested an underlying microvascular disease of the myocardium, based on normal findings on coronary angiogram (8) and the absence of coronary atherosclerosis upon histologic examination at autopsy (9)(10)(11)(12). However, clinical and subclinical coronary artery disease (CAD) is increasingly reported in SSc patients (13)(14)(15), although the prevalence of coronary atherosclerosis and the predisposing factors in SSc patients remain unknown.…”
mentioning
confidence: 99%